Ethical frameworks of “Tomorrow’s Business Leaders” - Dahl, Joan G. (International journal of value-based management, 1988)
This research explores the influence of five ethical frameworks on business students’ decision regarding the resolution of an ethical dilemma in a simulation. The frameworks of ethical tests are: Utilitarianism (the greatest good for the greatest number); Self-interest (maximizing the benefits to the individual); Categorical Imperative (universal principles of morality); Legality (rules, laws, etc.); and Light of Day (possibility of one’s actions being discovered). Results showed that the strongest influences were the Categorical Imperative, Self-Interest, and Legality. Among demographic variables, only age was related to the students’ decision or the ethical tests.